Transcriptome and Biochemical Analysis Jointly Reveal the Effects of Bacillus cereus AR156 on Postharvest Strawberry Gray Mold and Fruit Quality - Yu, Yi-Yang; Dou, Guo-Xia; Sun, Xing-Xing; Chen, Lin; Zheng, Ying; Xiao, Hong-Mei; Wang, Yun-Peng; Li, Hong-Yang; Guo, Jian-Hua; Jiang, Chun-Hao (Frontiers in Plant Science, 2021)
Postharvest strawberry is susceptible to gray mold disease caused by Botrytis cinerea, which seriously damaged the fruit storage capacity. Biological control has been implicated as an effective and safe method to suppress plant disease. The aim of this study was to evaluate the postharvest disease control ability of Bacillus cereus AR156 and explore the response of the strawberry fruit to this biocontrol microorganism. B. cereus AR156 treatment significantly suppressed gray mold disease and postpone the strawberry senescence during storage. The bacterium pretreatment remarkably enhanced the reactive oxygen-scavenging and defense-related enzymes activities. The promotion on expression of the encoding-genes was confirmed by qRT-PCR. Significantly increased expression of the marker genes of salicylic acid (SA) signaling pathway, PR1, PR2 and PR5, instead of that of jasmonic acid (JA)/ethylene (ET) pathway was also shown. Moreover, through transcriptome profiling, 6781 differentially expressed genes in strawberry upon AR156 treatment were identified. The GO classification and KEGG pathway enrichment indicated that AR156 altered transcription of numerous of transcription factors and genes involved in SA-related plant disease resistance, metabolism and benzoxazinoid and flavonoid biosynthesis. This study offered a non-antagonistic Bacillus as a method for postharvest strawberry storage and disease control, and further revealed that the biocontrol effects were arisen from induction of host responses on transcription level and subsequent resistance-related substance accumulation.